TINGKAT PENGETAHUAN MASYARAKAT DESA GANDIS HULU KECAMATAN DEDAI KABUPATEN SINTANG TERHADAP TUMBUHAN CIPLUKAN ( Physalis angulata L. ) DAN MANFAATNYA SEBAGAI ANTI DIABETES - Fadli Fadli; Randy Jaya Subakti (Akademi Farmasi Yarsi Pontianak, 2021)
Research has been conducted with the title of Knowledge level community gandis Hulu Sub District Dedai Sintang District against the plant plants (physalis angulata L.) and its benefits as an antidiabetic in March 2020. This study aims to determine the level of community knowledge of Gandis Hulu Village, Dedai District, Sintang District about the benefits of the Ciplukan plant as an antidiabetic. This type of research used a simple descriptive survey design with the population in this study were the people of Gandis Hulu Village, Gandis Hulu Hamlet RT 01 RW 00, Dedai District, Sintang District with 28 family cards with a total sample of 30 people. This study used a questionnaire consisting of 10 questions as a measure of the level of knowledge. The results showed that the respondents had knowledge about the ciplukan plant and its benefits as an antidiabetic with the level of knowledge possessed, namely good knowledge (20%), sufficient knowledge (50%) and insufficient knowledge (30%).